Life cycle assessment of self-healing products. (May 2022) - Cseke, Akos; Haines-Gadd, Merryn; Mativenga, Paul; Charnley, Fiona; Thomas, Bradley; Downs, Robert; Perry, Justin
Abstract: Self-healing products sense and repair damage and should help to improve product circularity and safety. Such products are at an early stage in research and development. Existing models for product life extension in life cycle assessment (LCA) were not developed for self-healing products. It is timely and urgent therefore to develop a framework for life cycle assessment for self-healing products so that their environmental impact can be optimised early at the design stage. This paper presents a new framework for LCA, based on a restoration of a product's function, and thus linking self-healing to product life extension and user acceptance. The model used within this framework uses the probabilities of self-healing, failure and user acceptance at the end of each life to quantify a product's service life extension and consequential avoided or delayed new production. The model takes into consideration multiple healing cycles with varying healing efficiencies. A case study scenario of self-healing propeller blades of an unmanned air vehicle employed for site inspection was used to test the application of the framework. The paper shows the positive contribution of self-healing in reducing life cycle impact. Sensitivity analysis revealed a tipping point where the benefits of avoided emissions outweigh the embedded impacts of self-healing technology. This clearly shows the importance of the life cycle assessment framework to understand under which conditions the environmental gains of using self-healing products are maximised.